All quiet on the Western front - Vansant, Wayne 1949-; Remarque, Erich Maria 1898-1970 (Dead Reckoning, 2019)
"Hailed by many as the greatest war novel of all time and publicly burned by the Nazis for being "degenerate," Erich Maria Remarque's masterpiece, All Quiet on the Western Front, is an elegant statement on a generation of men destroyed by war. Caught up by a romantic sense of patriotism and encouraged to enlist by authority figures who would not risk their lives to do the same, Paul Bäumer and his classmates join the fighting in the trenches of the Western Front in World War I. He is soon disenchanted by the constant bombardments and ruthless struggle to survive. Through years in battle, Paul and those he serves with become men defined by the violence around them, desperate to stay as decent as they can while growing more and more distant from the society for which they are fighting. This graphic novel recreates the classic story in vivid detail through meticulous research. The accurate depictions of uniforms, weapons, trenches, and death brings the horrors of the Western Front to life in a bold new way."--
"Based on the novel by Erich Maria Remarque, by arrangement with New York University." ; Comics in Farbe
Keywords: Remarque, Erich Maria -- 1898-1970 -- Im Westen nichts Neues; Remarque, Erich Maria / 1898-1970 / Im Westen nichts Neues / Adaptations; World War, 1914-1918 / Comic books, strips, etc; Graphic novels; Comic